Prevalence and correlates of depression and cognitive impairment among geriatric patients in a tertiary care hospital in Northern India: a cross-sectional study - Sharma, Shweta; Gupta, Abha; Satyam; Chaudhary, Garima (International Journal of Research in Medical Sciences, 2026)
Background: India’s rapidly aging population faces a significant burden of neuropsychiatric disorders, which are often underdiagnosed in primary care due to atypical presentations and a focus on physical ailments. This study aimed to quantify the prevalence of depression and cognitive impairment and elucidate their socio-demographic and clinical correlates in geriatric patients at a tertiary care hospital in Northern India. A hospital-based, analytical cross-sectional study was conducted over six months in the Medicine Outpatient Department. Methods: One hundred patients aged ≥60 years were recruited via consecutive sampling. Socio-demographic and clinical data were collected, and the geriatric depression scale-15 (GDS-15) and mini-mental state examination (MMSE) were used to assess depression and cognitive status, respectively. Results: The mean age was 74.7±6.8 years, with 60% male participants. Multimorbidity was highly prevalent (80%). The prevalence of depressive symptoms (GDS-15 ≥5) was 57%, predominantly mild. Cognitive impairment (MMSE <24) was present in 45% of the cohort. Coronary artery disease (CAD) was significantly correlated with higher depression scores. Diabetes mellitus and recent hospitalization were significantly associated with poorer cognitive performance, while higher educational attainment was a protective factor for cognition. Conclusions: There is a high burden of depression and cognitive impairment among geriatric outpatients, strongly linked with specific clinical conditions. Integrating routine screening for these disorders into primary care is essential for holistic geriatric health management.